2009 IEEE Globecom Workshops 2009
DOI: 10.1109/glocomw.2009.5360732
|View full text |Cite
|
Sign up to set email alerts
|

Low-Power Sleep Mode and Out-Of-Band Wake-Up for Indoor Access Points

Abstract: The expected massive adoption of indoor Access Points requires specific solutions to meet requirements for eco-sustainability regarding consumed power and radio interferences. Since Access Points are unused the main part of the day, application of a sleep mode mechanism is a promising approach. However, its implementation represents a radical change in mobile networking paradigm and requires innovative mechanisms to wake up the Access Points and thus rapidly restore the connectivity.Our approach uses an auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 6 publications
(5 reference statements)
0
26
0
3
Order By: Relevance
“…A number of studies showed that by considering a sleep strategy at a node during its inactivity, a certain amount of energy can be saved [2], [5], [9], [12], [13], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies showed that by considering a sleep strategy at a node during its inactivity, a certain amount of energy can be saved [2], [5], [9], [12], [13], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
“…operational power [24] Min. operational power [5] Transmit power [5] Energy for wake-up overhead [9] (42) Using Little's Theorem, the average packet delay is obtained as (43) Since a fraction of the arrivals is blocked due to the buffer overflow at the RSU, the utilisation of the system can be obtained as…”
Section: B Analytic Model For the Rsu With Various Types Of Sleep Cymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of Linksys WRG54G Wi-Fi access point (AP), the maximum reduction in the energy consumption that can be achieved is 28.57 % [2]. This value represents the energy consumption of Wi-Fi interface compared to the entire energy consumption of the access point.…”
Section: Introductionmentioning
confidence: 99%
“…In [2]. A low power sleep mode and an out of band wake-up mechanism has been adopted, a low power radio module to carry out of band control information is used to switch the WiFi AP into the sleep mode when no users exist.…”
Section: Introductionmentioning
confidence: 99%